Carbon Queen : the remarkable life of nanoscience pioneer Mildred Dresselhaus - Weinstock, Maia (Cambridge, Massachusetts : The MIT Press, 2022)
"The first biography of the late Mildred Dresselhaus, a pioneer of nanoscience, a champion for women in STEM, and recipient the Presidential Medal of Freedom and the National Medal of Science"--
Includes bibliographical references (pages 227-293) and index.
Keywords: Dresselhaus, M. S; Carbon; Nanotubes; Physicists -- Biography; Biographies